DETECTION OF PORK CONTAMINATION IN FRESH AND COOKED BEEF USING GENETIC MARKER MITOCHONDRIAL-DNA CYTOCHROME B BY DUPLEX-PCR - Ni'mah, A.; Kartikasari, Y.; Pratama, A. D.; Kartikasari, L. R.; Hertanto, B. S.; Cahyadi, M. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
By mixing with pork, beef adulteration is frequently found in the traditional  market that very disturbing Moeslem community in Indonesia. This study was conducted to detect pork contamination in fresh and cooked beef using genetic marker mitochondrial DNA cytochrome b (mt-DNA Cyt b) by duplex-PCR. A total of twelve samples was used in this study consisting six fresh meat samples and six cooked meat samples, respectively. Those beef and pork were bought from animal slaughterhouse and a supermarket in Surakarta. Cooked samples were prepared by boiling the meats in hot water at 100oC for 30 minutes. We designed pork contamination in beef in the level of 0, 1, 5, 10, 25%, respectively. The DNA genome was extracted and polymerase chain reaction (PCR) was performed using species specific primer to isolate mt-DNA Cyt b gene from the samples. The results showed that the DNA genome was successfully extracted from pork, beef, and contaminated meat samples. In addition, visualization of duplex-PCR on 1.5% agarose gel was able to detect pork contamination in both fresh and cooked beef up to very small proportion (1%). The existence of pork in beef was indicated with the presence of specific 398 bp DNA band. It can be concluded, duplex-PCR of mt-DNA Cyt b gene was very sensitive in detection of pork contamination in fresh and cooked beef.